Наука як феномен цивілізації - Кримський, С. (Вісник НАН України, 2003)
У наш час наука виконує функцію свого роду «нервової системи» планетарної цивілізації. В статті аналізуються базові принципи науки, робиться спроба визначити критерії науковості. Nowadays science has the function of the so-called «nervous system» of the planetary civilisation. In the article the author analyses basic principles of science as well as makes an attempt to determine the criteria of scientific character.